PENGARUH TERPAAN TAYANGAN PROGRAM NET.86 DI TELEVISI TERHADAP CITRA POLISI DALAM PERSPEKTIF MASYARAKAT KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Wanda Wahyudi Wahyudi; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is motivated by the proliferation of cases related to the image of the police as the shooting between the members of the police, clashes between police and students or the Commission as well as cases of police being caught using drugs and so forth. This gives rise to a negative impression of the community as well as a bad view of the police. Overcoming these problems, now the police as well as presenting television media impressions Net.86 program that can be watched by the entire community in Indonesia to look at a variety of police activities while on duty. This study aims to analyze how much influence exposure to impressions Net.86 program on television the image of the police in the community perspective Marpoyan Peace District of the city of Pekanbaru.The method used in this research is descriptive quantitative. Quantitative research is research in the form of data obtained from the respondents that had been collected, processed and analyzed using statistical theory as a means of solving problems, so this method will provide certainty in decision making. Collecting data using questionnaires and documentation. The population in this study is that people Marpoyan Peace District of the city of Pekanbaru, amounting to 34 908 households. The sample in this study amounted to 100 respondents were obtained based on the formula slovin while the sampling technique used is purposive sampling. Measurement data using a Likert scale. Data analysis techniques used in this study is a simple linear regression.The results showed sig. 0,000 obtained by measurement through SPSS version 24.0 is smaller than the probability of 0.05, thus it can be concluded that the independent variable (Exposure to Impressions Net.86) significantly influence the dependent variable (Citra Police) or Ha accepted and H0 is rejected. Net.86 impressions programs have influence proportion of 50.3% against the image of police in the community perspective Marpoyan Peace District of Pekanbaru city, while the remaining 49.7% is influenced by other variables not examined in this study